Synthesis of poly (styrene-co-maleic anhydride)-based zwitterionic copolymers for nanodisc formation - Sibariboyi, Sinothando (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.